Rocky flats nuclear plant: how positive leadership prevented a radioactive disaster - Cameron, Kim (Henry Stewart Talks, 2016)
The case study addresses the virtuous and positive practices of a company that cleaned up Rocky Flats Nuclear Plant, the most dangerous buildings in America, while excelling beyond expectations of intimidating deadlines, budgets, and work and safety regulations.
Reviewed at 2016/08/31